2018
DOI: 10.1177/0004563218811365
|View full text |Cite
|
Sign up to set email alerts
|

Rapid liquid chromatography tandem mass-spectrometry screening method for urinary metabolites of primary hyperoxaluria

Abstract: Background The primary hyperoxalurias are inherited disorders of glyoxylate metabolism that lead to overproduction of oxalate, urolithiasis and renal failure. Delays in diagnosis can be costly in terms of preserving renal function. Here we present a rapid liquid chromatography tandem mass-spectrometry screening method for the analysis of metabolites (primary hyperoxaluria metabolites) produced in excess by primary hyperoxaluria patients that include glycolate, glycerate and 2,4-dihydroxyglutarate. Methods Assa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 15 publications
0
4
0
Order By: Relevance
“…Unfortunately, the methodology used to ascertain this result was not recorded, but it has been shown by distribution of external quality assurance material that methods for urine organic acids may give false-negative results for glycerate as a consequence of the poor extraction of this analyte. The development of more specific methodologies 25,32 should make this less likely to occur but is currently affected by the lack of certified reference materials and internal standards. Demonstration of glyceric aciduria will allow focusing of genetic testing; however, the combination of CKD5 and elevated urine oxalate excretion should not exclude consideration of PH2.…”
Section: Discussionmentioning
confidence: 99%
“…Unfortunately, the methodology used to ascertain this result was not recorded, but it has been shown by distribution of external quality assurance material that methods for urine organic acids may give false-negative results for glycerate as a consequence of the poor extraction of this analyte. The development of more specific methodologies 25,32 should make this less likely to occur but is currently affected by the lack of certified reference materials and internal standards. Demonstration of glyceric aciduria will allow focusing of genetic testing; however, the combination of CKD5 and elevated urine oxalate excretion should not exclude consideration of PH2.…”
Section: Discussionmentioning
confidence: 99%
“…Concentrations of plasma oxalate in PH patients can overlap with those of patients seen in renal failure from any cause [3,4] and therefore are not always diagnostic for PH. However, in CKD stage 4 or greater, values > 50 µmol/L are often observed in PH and is thus highly suggestive of the diagnosis and warrants further diagnostic testing: urinary PH metabolites (glycolate, glycerate and dihydroxyglutarate [5]) and genetic testing for the 3 known causative genes (AGXT, GRHPR, HOGA1) [6].…”
Section: Introductionmentioning
confidence: 99%
“…• Check thyroid stimulating hormone and thyroxine levels at least yearly; more frequently if after treatment • Check 25-hydroxy vitamin D levels at least yearly • In teenagers and adults, be aware of the risk of hypogonadism markers of PH3; however, HOG is unstable 34 and can lead to false negative results 35 whereas DHG has 100% sensitivity 36 . Comparison of results between laboratories is currently impossible for these analytes as no international calibrators exist and one must therefore rely on local reference ranges.…”
Section: Endocrine Functionsmentioning
confidence: 99%
“…Data on the impact of liver transplantation among patients with PH2 are scarce owing to the rarity of the disease and the assumed better outcome of these patients compared with patients with PH1. However, a 2019 study of 101 patients with PH2 found that 22 patients reached stage 5 CKD at a median age of 40 (34)(35)(36)(37)(38)(39)(40)(41)(42)(43)(44)(45)(46)(47)(48) years of age. Ten of these 22 patients underwent isolated kidney transplantation, for which 1-year and 5-year cumulative kidney allograft survival (censored for death) were only 43% and 29%, respectively 2 .…”
Section: Rationale For Transplantationmentioning
confidence: 99%